Analisis Struktur, Perilaku dan Kinerja Pasar Komoditi Paprika (Studi Kasus : Wijaya Farm di Kecamatan Baturiti Kabupaten Tabanan Provinsi Bali) - FARHANI, NADYA; DEWI, IDA AYU LISTIA; SUTARI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Analysis of Structure, Conduct, and Performance of the Bell Pepper Commodity Market (Case of Study: Wijaya Farm in Baturiti District, Tabanan Regency, Bali Province).  Bell pepper is one of the horticultural crops that has the potential to be developed in Indonesia, indicated by the high demand for bell pepper from various consumer backgrounds but has not been matched by anticipatory development efforts towards market behavior, where Wijaya Farm is still difficult to implement an effective marketing system for bell pepper commodities. The purpose of this research is to analyze the structure, conduct and market performance of paprika commodity at Wijaya Farm. The research method used is market structure analysis with the degree of market concentration and product differentiation, and market behavior is analyzed by describing the pattern of marketing channels and marketing functions, market performance is analyzed by calculating marketing margins and marketing efficiency. The results show that the market structure is oligopoly. The market conduct shows that there are three patterns of marketing channels, channel I (Wijaya Farm, retailers, end consumers), channel II (Wijaya Farm, restaurants, end consumers) and channel III (Wijaya Farm, household consumers). The market performance shows that the total margin on channel I is Rp 11,670.00, margin on channel II is Rp 19,500.00 and channel III is Rp 00.00. Channel I had the smallest percentage of marketing efficiency that is equal to 2.88%, so that channel I is the most efficient channel.